Genetic testing confirmed osteopetrosis with initial presentation of nystagmus - Kai-Yen Chiu; Yu-Yang Lin; Yao-Lin Liu; Ni-Chung Lee; Tzu-Hsun Tsai (Taiwan Journal of Ophthalmology)
Osteopetrosis (OS) is a rare heritable disorder characterized by osteoclast dysfunction and increased bone density on radiography. Optic nerve osseous compression is the most frequent ocular complication of OS, with nystagmus, strabismus, ptosis, proptosis, and lagophthalmos occurring less frequently. However, it is uncommon for patients to have neurological or ocular symptoms at initial presentation. Herein, we present the case of a 3-year-old girl with the initial presentation of ocular symptoms who was confirmed to have OS through genetic testing. She was born full-term and found to have nystagmus since the age of 1 year. Her best-corrected visual acuity was 1.2/60 for both eyes. Exotropia of the left eye and bilateral small-amplitude pendular nystagmus were also noted. Color fundoscopy revealed a tessellated fundus and pale discs with cup-to-disc ratios of 0.5–0.6. Magnetic resonance imaging revealed bilateral optic canal stenosis and optic nerve atrophy. Whole-exome sequencing revealed a biallelic chloride voltage-gated channel 7 mutation, c.2297T > C (p.Leu766Pro) and c.1577G > A (p.Arg526Gln), and autosomal recessive OS was diagnosed. The patient is currently being evaluated for possible hematopoietic stem cell transplantation. We suggest that OS should be considered a differential diagnosis for unexplained nystagmus and optic nerve atrophy.